THE MODEL OF INTELLECTUAL CAPITAL AND PERFORMANCE - Bahtiar, Bahtiar; Yudi Yulius; Anoesyirwan Moeins (Dinasti International Journal of Management Science, 2022)
This research focused on higher of job rejection result and low of coordination among unit in problem solving of all the projects which is tend to decline of employee’s performance. The main issues discussed in this research is factors influence it, namely human procurement, development and intellectual capital. The research aims to analyze, describe and test the impact of human procurement, development on intellectual capital and its implication on employee’s performance at PT. Garuda Indonesia. The research used was descriptive and explanatory survey method, so the research attempts to collect, present, analyze, and test hypotheses, to make a conclusion were used Structural Equation Model (SEM) approach. The design of study is a survey research, the unit analysis selected were core knowledge worker with a sample size of 303 from 1245 employees, based on Slovin’s formula. The results indicated that human procurement, development have a simultaneously positive and significant effect on intellectual capital, and human procurement, development is either partially or simultaneously have a positive and significant effect on employee’s performance level through intellectual capital. The findings are: (1) human procurement indicates low contribution on either intellectual capital or employee’s performance, the highest score of human procurement dimension is selection and the lowest is recruitment dimension. 2) human development indicates low contribution on either intellectual capital or employee’s performance, the highest score of human development dimension is education and the lowest is training dimension (3) intellectual capital indicates moderate scores on employee’s performance level, the highest score of intellectual capital dimension is social capital and the lowest is structure capital dimension. (4) the highest score size of employee’s performance dimension based on employees perception is goal and the lowest is motive dimension.